Case Report: Testicular Sarcoidosis: The Diagnostic Role of Contrast-Enhanced Ultrasound and Review of the Literature - De Cinque, Antonio; Corcioni, Beniamino; Rossi, Martina Sofia; Franceschelli, Alessandro; Colombo, Fulvio; Golfieri, Rita; Renzulli, Matteo; Gaudiano, Caterina (Frontiers in Medicine, 2021)
Sarcoidosis is a multisystemic disease histologically characterised by non-caseating epithelioid granulomas and multinucleated giant cells; the etiology is still uncertain, and likely related to a complex interplay between environmental and genetic factors. The genitourinary system is affected in fewer than 0.2% of all clinically diagnosed cases of sarcoidosis and in 5% of those identified in autopsy studies. In this report, we describe a case of a 42–year-old male with one hypoechoic lesion per testis on B-mode evaluation; contrast-enhanced ultrasound (CEUS) on both lesions was carried out. During the early phase, the masses showed a hypovascular appearance as compared to the surrounding testicular tissue, maintaining the hypo-enhancement in the late phase. Tissue biopsy for pathological evaluation confirmed testicular sarcoid involvement, showing non-caseating granulomas. Allowing visualisation of testicular microvascularisation, CEUS may play an important role in excluding malignancy, avoiding unnecessary aggressive treatment for benign conditions, such as sarcoidosis. A review of the literature of reported cases since 2004 of sarcoidosis involving the testis is also included.